(untitled) (Research, Society and Development, 2021)
Objective: Analyze the burden of cardiovascular risk factors and mortality among men and women diagnosed with STEMI in the state of Sergipe. Method: Cross-sectional, quantitative study, developed between December/2014 and March/2017. Data were collected at hospitals in Sergipe, using their own instrument, information from medical records and interviews. The analysis performed using the Person test and the Student t test. Ethics and Research Committee of UFS number 483.749. Results: Of the total number of patients analyzed in the study (707), it was identified that women were older (p = 0.035). Systemic arterial hypertension (p = 0.001) and dyslipidemia (p<0.001) were more frequent in women and smoking in men (p = 0.592). Mortality was higher in females than males (p = 0.027). Conclusion: Knowing the clinical-epidemiological profile and risk factors enables early intervention and encourages the effectiveness of treatment in both sexes.